SMART GOVERNMENT MONITORING POPULATION ADMINISTRATION IN GATTARENG TOA VILLAGE, MARIORIWAWO SUBDISTRICT, SOPPENG DISTRICT - Tasmil Tasmil (Journal of Information Technology and Its Utilization, 2018)
This study aims to design and apply smart government monitoring of population administration applied by using Hypertext Preprocesor (PHP), MySql and C# with online server in Gattareng Toa Village, Marioriwawo Subdistrict, Soppeng District This data is obtained through (1) Field Research (2) Research Library (3) Interview. Data were analyzed by pieces analysis. The results of the study  indicated that the Smart Government Monitoring Population Administration can help the system of population administration work in monitoring Population Administration in Gattareng Toa Village, Marioriwawo Subdistrict, Soppeng District